A PAPR Reduction in FBMC-OQAM System via Overlapping-PTS with Artificial Bee Colony Phase Optimization - Panya Jirajaracheep; Tanairat Mata; Pisit Boonsrimuang (My University, 2019)
In this paper, the overlapping Partial Transmit Sequence (overlapping-PTS) with Artificial Bee Colony (ABC) phase optimization method is proposed to reduce the larger Peak-to-Average Power Ratio (PAPR) which is the major drawback of filter bank multicarrier with offset quadrature amplitude modulation (FBMC-OQAM) system.In this proposed method, we clarify the problem of larger PAPR by reducing the PAPR of each overlapping data symbol with lower combination of the optimal phase factors.Unlike the conventional PTS methods, the proposed method uses the lower combination of phase factors by applying the ABC algorithm with considering the overlap between the current data symbol and the past data symbol to search the optimal phase combination.The proposed overlapping-PTS with ABC phase optimization method can significantly reduce the larger PAPR with low computational complexity for the FBMC-OQAM system which can be verified by the computer simulation results.From the computer simulation results, it can be confirmed that the proposed method shows much better PAPR which can reduce the PAPR by approximately 1.9 dB at CCDF 10 -1 as comparing with the conventional PTS method and can perform much lower computational complexity than the conventional methods which are only 4.38% and 0.76% for S phase factor pattern =300 and 50 respectively.
Keywords: Filter bank; QAM; PAPR reduction in OFDM